Antibacterial harziane diterpenoids from a fungal symbiont Trichoderma atroviride isolated from Colquhounia coccinea var. mollis. (February 2020) - Li, Wen-Yuan; Liu, Yan; Lin, Yu-Tian; Liu, Yan-Chun; Guo, Kai; Li, Xiao-Nian; Luo, Shi-Hong; Li, Sheng-Hong
Abstract: Fungal endophytes from plants are an important source for discovery of novel bioactive natural products. In this study, five undescribed harziane diterpenoids with a 4/7/5/6 tetracyclic scaffold, harzianols F‒J and three known derivatives, were obtained from the liquid fermentation of an endophytic fungus Trichoderma atroviride B7, which was isolated from the healthy flower of a Lamiaceae plant Colquhounia coccinea var. mollis . Their structures were elucidated by comprehensive spectroscopic analyses and X-ray crystallographic diffraction in the case of harzianol F. Harzianol I exhibited significant antibacterial effect against the growth of Staphylococcus aureus (EC50 = 7.7 ± 0.8 μg/mL), Bacillus subtilis (EC50 = 7.7 ± 1.0 μg/mL), and Micrococcus luteus (EC50 = 9.9 ± 1.5 μg/mL). Meanwhile, cytotoxic activity of harzianol I against three cancer cell lines was also observed. A plausible biosynthetic pathway for harziane diterpenoids was proposed. Graphical abstract: Five undescribed harziane diterpenoids and three known derivatives were obtained from an endophytic fungus Trichoderma atroviride B7 that was isolated from a Lamiaceae plant Colquhounia coccinea var. mollis . One of them showed significant antibacterial and moderate cytotoxic activities. Image 1 Highlights: Eight harzianes were obtained from plant endophytic fungus Trichoderma atroviride. Five diterpenoids were previously undescribed. All diterpenoids possess a rare and complex 4/7/5/6 tetracyclic scaffold. Antibacterial and cytotoxic activities of one diterpenoid were observed. A plausible biosynthetic pathway for harziane diterpenoids was proposed.